A ruse of reason: constitutionalist powers in the work of Michel Foucault - Sharman, Adam (1995)
The thesis begins by examining the philosophical underpinnings of Foucault's 'constitutionalist' methodology. It argues that the archaeological method of The Order of Things derives principally neither from phenomenology nor structuralism, but from a philosophical and scholarly tradition (that of Kant, Cassirer, Duhem, Koyré) in which mathematics, the scientific revolution of Galileo et al, and an a priori conceptualism are paramount. It suggests that the rigid gathering of conceptual energies into the notion of episteme finds an echo in the subsequent genealogical work on prisons. The thesis challenges the widely-held view that Foucault is a Nietzschean thinker, maintaining that his overstatement of the constitutionalist powers of 'discipline' is conditioned as much by a strong Cartesianism as by his residual structuralism. The thesis shows how the Classical theme of order informs Foucault's attempt to develop a modern theory of the constitution of the subject in discourse. It postulates that the much-traduced first volume on sexuality, which introduces time into his theory and embraces many of the truisms of twentieth-century theoretical science, exhibits a less rigid understanding of constitutionalist powers. The penultimate chapter addresses, in the context of accusations of Eurocentrism levelled at Foucault's work, some of the shortcomings of theoretico-political work which fails to think through the 'deconstitution' of power, the play between order and disorder. Finally, a profound continuity is posited between the archaeological method of The Order of Things and his treatment of sexuality. Rejecting the suggestion of an epistemological break, the thesis discovers the strategic invocation, in the final two volumes, of a very traditional understanding of reason. Diverging from those critics who only hear in Foucault the insistent theme of specificity and the persistent denunciation of reason and (technological) rationality, the thesis maintains that his writings effect a constant appeal to logos as order and reason.